Low Mg content on Ti-Nb-Sn alloy when in contact with eBMMSCs promotes improvement of its biological functions - Carolina da Silva Dias (Springer, 2021)
Abstract Magnesium is a metal used in the composition of titanium alloys and imparts porosity. Due to its osteoconductive, biocompatible and biodegradable characteristics, its application in the development of biomedical materials has become attractive. This study aimed to evaluate the influence of magnesium present in porous Ti-Nb-Sn alloys, which have a low elastic modulus in adhesive, osteogenic properties and the amount of reactive intracellular oxygen species released in mesenchymal stem cells derived from bone marrow equine bone (eBMMSCs). Mechanical properties of the alloy, such as hardness, compressive strength and elastic modulus, were analyzed, as well as surface morphological characteristics through scanning electron microscopy. The evaluation of magnesium ion release was performed by atomic force spectroscopy. The biological characteristics of the alloy, when in contact with the alloy surface and with the culture medium conditioned with the alloy, were studied by SEM and optical microscopy. Confirmation of osteogenic differentiation by alizarin red and detection of ROS using a Muse® Oxidative Stress Kit based on dihydroetide (DHE). The alloy showed an elastic modulus close to cortical bone values. The hardness was close to commercial Ti grade 2, and the compressive strength was greater than the value of cortical bone. The eBMMSCs adhered to the surface of the alloy during the experimental time. Osteogenic differentiation was observed with the treatment of eBMMMSCs with conditioned medium. The eBMMSCs treated with conditioned medium decreased ROS production, indicating a possible antioxidant defense potential of magnesium release.